Can paper mulberry contribute to building sustainable rural livelihoods in northern Laos? - Andreas Neef (2018)
Most ethnic minority villages in northern Lao PDR continue to rely on non-timber forest products (NTFPs) for much of their subsistence and cash economy. Paper mulberry (Broussonetia papyrifera) is an important NTFP in many parts of northern Laos, providing opportunities for earning cash income, particularly for women. Since the plant has been successfully domesticated by local people, it has also been widely proposed as the basis for a sustainable agro forestry system. The major objectives of this article are to investigate the production, processing and marketing system of paper mulberry and to assess its potential to contribute to building sustainable rural livelihoods in northern Lao PDR. We also elucidate how this perennial plant has been affected by recent government policies, changes in resource management - from gathering to domestication - and current land use transitions, drawing on a case study from PhaOudom district, Bokeo province, northern Laos. Whether a sustainable production and supply-chain management system for paper mulberry can be developed that provides a reliable - albeit modest - source of income for many ethnic minority villagers in northern Laos will largely depend on the capacity of local producers to enhance product quality and to become more active and equal actors in the value chain, but most of all on the political will of the Lao government to rethink its controversial agriculture and forest policies that aim at reducing agricultural diversity and restrict access to NTFPs through resettlement of formerly forest-dependent communities.